Prenatal developmental toxicity study of herbal tea of Moringa stenopetala and Mentha spicata leaves formulation in Wistar rats. (2022) - Musa, Abdu Hassen; Gebru, Girmai; Debella, Asfaw; Makonnen, Eyasu; Asefa, Mesfin; Woldekidan, Samuel; Abebe, Abiy; Lengiso, Boki; Bashea, Chala
Abstract: Background: Moringa stenopetala and Mentha spicata have long been used to treat diabetes, hypertension, asthma, and other ailments. Herbal tea of M. stenopetala and Mentha spicata leaves formulation showed better antidiabetic and antihypertensive activities. This study investigated the prenatal developmental toxicity potential of the herbal tea of M. stenopetala and M. spicata leaves blend in rats. Methods: Wistar pregnant rats were randomly distributed into four groups (n = 8). Group I (control) dams received distilled water. Group II-IV dams were treated with 559.36, 1118.72, and 2237.44 mg/kg of herbal tea of M. stenopetala and Mentha spicata leaves formulations, respectively, during days 5–19 of gestation. Maternal mortality, clinical signs, body weight changes, and food consumption were recorded. On gestation day 20, cesarean sections were performed, and maternal parameters of systemic toxicity (e.g., body weight, serum biochemistry, organ weight, and macro-pathology) as well as reproductive toxicity (e.g., number of corpora lutea, implantations, resorptions (early/late), pre/postimplantation losses, number of fetuses (live/dead), and fetal body weights, length, and their sex ratio) were evaluated. Fetuses were further examined for external, soft tissue, and skeletal alterations. Results: No herbal tea-related maternal deaths or overt toxic symptoms were observed. The measured maternal systemic and reproductive toxicity parameters showed no herbal tea-associated significant alterations at any dosage levels. Moreover, there were no overt toxic effects of the herbal tea on the fetal external, visceral, or skeletal prenatal growth and development. Conclusion: The study findings demonstrated that the herbal tea of M. stenopetala and M. spicata leaves blend could be relatively safe/low toxic to pregnant rats and developing fetuses. The no-observed-adverse-effect level (NOAEL) of herbal tea for maternal toxicity, fetotoxicity, and teratogenicity in rats is estimated to be > 2237.44 mg/kg/day. Graphical Abstract: ga1 Highlights: We assessed the prenatal developmental oral toxicity of herbal tea of M. stenopetala and M. spicata leaves blend in rats. Toxicity parameters of the pregnant rats and developing fetuses were investigated. The evaluated maternal and fetal toxicity parameters showed no significant variations between the test and control groups.